ENHANCING EARLY CHILDHOOD EDUCATORS' KNOWLEDGE IN MEASURING THE NUTRITIONAL STATUS OF YOUNG CHILDREN - Fahmi, Ilmia; Maulidiana, Annisa Rizky; Ariestiningsih, Ayuningtyas Dian; Wirawan, Nia Novita (Caring: Jurnal Pengabdian Masyarakat, 2024)
Early childhood educators are one of the main elements in providing appropriate stimulation and monitoring the growth and development of children aged 0 - 6 years so that they do not experience nutritional and health problems, for example stunting. Early childhood growth, especially weight and height, is very important to monitor through routine monthly measurements and determining nutritional status using a growth curve. Early childhood educators face several obstacles in carrying out nutritional status monitoring activities, such as teachers' lack of knowledge and skills in carrying out anthropometric measurements, the use of growth curves to determine nutritional status and limited equipment. The aim of this community service is to increase the knowledge of the educators in Malang Regency, especially Pakisaji sub-district, to measure and monitor the nutritional status of preschool children. Community service activities were carried out on early October 2023 at the Nutrition Department and were attended by 44 participants. Before the activity begins, participants first fill out a pre-test form to determine their level of knowledge. Participants are given education about the correct way to measure nutritional status in early childhood. A total of 39 participants completed the pre-test and post-test completely with an average pre-test score of 43.72 and post-test 75.13, an increase in score of 30 points. It can be concluded that community service activities increase the knowledge and skills of the educators in measuring the nutritional status of early childhood.